Closing the loop in building services: A systematic review of circular economy applications - Itanola, Moses; Griffiths, Philip; Motawa, Ibrahim (Building services engineering research & technology, 2025)
The substantial environmental impact of buildings has garnered significant attention. However, sustainability efforts often prioritise structural and envelope materials, overlooking building services - systems for ensuring occupants’ safety and comfort. Given their complexity, rapid technological advancements, and substantial costs, these components necessitate a circular economy approach to optimise resource utilisation. This study conducts a systematic literature review to assess the current state of circular economy implementation in building services, identifying barriers, opportunities, key influencers, and potential strategies. Findings indicate that applying circular economy principles within building services remains nascent. Barriers encompass technical, economic, legislative, and organisational challenges. Conversely, numerous opportunities exist, alongside six key influential stakeholders. The analysis enabled the development of a framework to integrate existing principles and building blocks with identified essential strategies for advancing circular building services. The integrated strategies include design, business models, policy, product information, warranties, life cycle costing, digital technology, education, collaboration, and transparency. This study recognises various research gaps and highlights the need for further exploration to realise the full potential of circular economy in building services. Ultimately, a shift in mindset, coupled with new skills and holistic approaches, is required to drive progress in this domain. Practical application The application of circular economy in building services is still nascent, representing a missing piece for advancing sustainable construction. This paper examines the existing knowledge in this domain to identify barriers, opportunities, and key influencers. The strategies identified enabled a framework for advancing circular building services. The study is vital for engineers, designers, researchers, policy makers, and all other stakeholders to advance circularity in the building services sector.